Plasma P-tau181 in Alzheimer’s disease: relationship to other biomarkers, differential diagnosis, neuropathology and longitudinal progression to Alzheimer’s dementia - Janelidze, Shorena; Mattsson, Niklas; Palmqvist, Sebastian; Smith, Ruben; Beach, Thomas G.; Serrano, Geidy E.; Chai, Xiyun; Proctor, Nicholas K.; Eichenlaub, Udo; Zetterberg, Henrik; Blennow, Kaj; Reiman, Eric M.; et al. (Nature medicine, 2020)
Plasma phosphorylated tau181 (P-tau181) might be increased in Alzheimer’s disease (AD), but its usefulness for differential diagnosis and prognosis is unclear. We studied plasma P-tau181 in three cohorts, with a total of 589 individuals, including cognitively unimpaired participants and patients with mild cognitive impairment (MCI), AD dementia and non-AD neurodegenerative diseases. Plasma P-tau181 was increased in preclinical AD and further increased at the MCI and dementia stages. It correlated with CSF P-tau181 and predicted positive Tau positron emission tomography (PET) scans (area under the curve (AUC) = 0.87–0.91 for different brain regions). Plasma P-tau181 differentiated AD dementia from non-AD neurodegenerative diseases with an accuracy similar to that of Tau PET and CSF P-tau181 (AUC = 0.94–0.98), and detected AD neuropathology in an autopsy-confirmed cohort. High plasma P-tau181 was associated with subsequent development of AD dementia in cognitively unimpaired and MCI subjects. In conclusion, plasma P-tau181 is a noninvasive diagnostic and prognostic biomarker of AD, which may be useful in clinical practice and trials. Plasma P-tau18 level increased with progression of Alzheimer’s disease (AD) and differentiated AD dementia from other neurodegenerative diseases, supporting its further development as a blood-based biomarker for AD.